UPAYA GURU KE-NU-AN DALAM MENANAMKAN NILAI-NILAI ASWAJA PADA PESERTA DIDIK DI SMP ISLAM NGADIREJO TEMANGGUNG - Khifti Maulaya Falakhi; Ngarifin Shidiq; Vava Imam Agus Faisal (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
This study aims to determine the efforts of Ke-NU-an teachers in instilling the values of Ahlussunnah Wal Jama'ah in students at SMP Islam Ngadirejo. In addition, it is also to find out the results obtained in the efforts of NU-an teachers in instilling the values of Ahlussunnah Wal Jama'ah in students at SMP Islam Ngadirejo, as well as to find out the supporting and inhibiting factors. Qualitative field research uses observation, interview and documentation methods in data collection. Then the analysis technique uses data collection techniques, data reduction, data presentation and conclusion drawing and verification. The results showed that: 1) Teachers' efforts in instilling Aswaja values in students by instilling Aswaja values in the style of NU-an every day, religious extracurricular activities, IPNU and IPPNU organizations, as well as teaching Aswaja to NU-an in the classroom. 2) the results obtained in the process of instilling Aswaja values in students, namely the more accustomed students are in carrying out various Aswaja amaliyah-amaliyah to NU-an. 3) supporting factors in the process of instilling Aswaja values in students, namely SMP Islam Ngadirejo Temanggung is a school under the auspices of LP Ma'arif NU, then support from school culture that is still thick with Aswaja values, then support from teachers who are competent in ovating students in instilling Aswaja values, as well as support from facilities and infrastructure that can facilitate the learning process. While the inhibiting factors are the external environment (family environment and community environment) and the time in the learning process is short.